2016
DOI: 10.1093/ofid/ofw129
|View full text |Cite
|
Sign up to set email alerts
|

Household Clustering of Escherichia coli Sequence Type 131 Clinical and Fecal Isolates According to Whole Genome Sequence Analysis

Abstract: In a whole genome-based phylogeny, clinical and fecal isolates of Escherichia coli sequence type 131 (H30R1 and H30Rx subclones) from six households formed household-specific clusters, interspersed among reference ST131 genomes. This supported the fecal-urethral hypothesis and confirmed within-household strain sharing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
51
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 38 publications
7
51
0
Order By: Relevance
“…This study has shown that in about half of such cases, this is due to the immigration and establishment of strains and not within‐host evolution. Thus, the results of this study show that despite hosts being regularly exposed to a diversity of E. coli through the food that they consume and the individuals they associate with (Blyton et al ., ; Johnson et al ., ), factors related to the host, at least in part, determine what E. coli strains succeed in establishing.…”
Section: Discussionmentioning
confidence: 99%
“…This study has shown that in about half of such cases, this is due to the immigration and establishment of strains and not within‐host evolution. Thus, the results of this study show that despite hosts being regularly exposed to a diversity of E. coli through the food that they consume and the individuals they associate with (Blyton et al ., ; Johnson et al ., ), factors related to the host, at least in part, determine what E. coli strains succeed in establishing.…”
Section: Discussionmentioning
confidence: 99%
“…The fully assembled reference genomes for JJ1886 (NC_022648 [80]) and JJ1887 (NZ_CP014316 [81]) were aligned to each other using Progressive Mauve (82) and inspected for large-scale rearrangements, inversions, and duplications. Candidate sequence variations were reported directly from the alignment and confirmed by mapping raw Illumina reads obtained for those genomes (11,16) to the assembled reference sequences using Bowtie 2 (83). The alignments were refined using SAMtools (84).…”
Section: Methodsmentioning
confidence: 99%
“…For SNP analysis, raw Illumina sequencing reads (16) were aligned to the reference genome (JJ1886 or JJ1887) using the BWA-MEM algorithm (85). The alignments were refined with SAMtools (84), and variants were called using BCFtools (http://www.htslib.org).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations